Kesenjangan Regulasi Pembuktian Elektronik di Era Society 5.0: Analisis Putusan PA Sungailiat dan Efektivitas Regulasi Mahkamah Agung - Siti Fatiya Hasanah; Nabila Mersita; Mesya Assauma Nurfitrah (CV. ITTC INDONESIA, 2026)
Entering the Society 5.0 era, digital transformation in the judicial system demands comprehensive procedural law readiness. This study aims to analyze the legal standing and evidentiary strength of electronic evidence and identify procedural challenges in practice. The research method employed is legal normative with a statute approach and a case approach, specifically analyzing the Sungailiat Religious Court Decision Number 0190/Pdt.G/2020/PA.Sglt. The results indicate that although Law Number 1 of 2024 (Second Amendment to the ITE Law) provides strong legitimacy for digital evidence, a regulatory gap persists in practice. Internal regulations of the Supreme Court, such as PERMA Number 7 of 2022 and SEMA Number 1 of 2014, are considered ineffective as they focus primarily on administrative aspects and have yet to address technical standards for authentication and verification of electronic evidence. Findings from the Sungailiat decision confirm that the absence of standard operating procedures causes the assessment of electronic evidence to rely entirely on judicial discretion, which often leads to the disregard of the digital evidence's material strength for the sake of substantive justice. Therefore, a reform of civil procedural law is necessary to regulate forensic audit standards and specific electronic evidence governance to ensure legal certainty in the digital judiciary era.